To the estimation of the ground waters pollution danger on the basis of studing of water balance elements (on the data of water-balance station Malaya Istra) - Yu. Yu. Alentyev; A. B. Lisenkov (Известия высших учебных заведений: Геология и разведка, 2015)
The possibiltty of the use of information about the conditions of formation of water balance elements for the estimation of the potencial danger of ground waters pollution is justified. The modeling of average elements of water balance for many years on the territory of Istrinsky district has been implemented in the programm SurfBal. Under the modeling the meteorological data for the average daily temperature, atmospheric deposits and sunny radiation for the many years period, obtained on the forest meteostation of water-balance station Malaya Istra has been taken into account as well as the value of flow, calculated due to the vegetation and lithological composition, the index of snow melting, the index of leaf surface growth and other data. In result the estimate values of balance elements on the territory of forest massifes were obtained, which were used in the estimation of the possibiltity of water pollution. The investigation is esspecially actual due to the situation of the decrease of the forest areas in Moscow region under the natural reasons, fires, santtary cutting and for buildtng purposes.